Faktor yang Berhubungan dengan Kejadian Gastritis di Puskesmas Biru Kabupaten Bone - Surya Darmawan Syam; A. Arsunan Arsin; Jumriani Ansar (Hasanuddin Journal of Public Health, 2020)
Gastritis is experienced by many Indonesians ranging from adolescence to old age. In Bone District in 2018 there were 20,792 cases and 60 deaths. This study aims to determine the factors associated with the occurrence of gastritis at ​​Puskesmas Biru in Bone Regency in 2019. This type of research is observational analytic using cross-sectional study design. The Population in this research were visitors to the general clinic of Puskesmas Biru during January – August 2019 with total of minimum sample is 235 people by using the sampling technique was accidental sampling. Research was held in Puskesmas Biru from October to November 2019. Data were analyzed univariate and bivariate using chi square test. The results of the study showed that the number of respondents suffering from gastritis was 79 people (33.6%). Chi square test results showed that the type of food (p=0.001), stress (p=0,000), and NSAIDs consumption (p=0,000) were factors associated with gastritis. While the frequency of eating (p=0.053), coffee consumption (p=0.787), and smoking habits (p=0.319) were not factors associated with the occurrence of gastritis. There is a relationship between the type of food, stress, and NSAIDs consumption with the occurrence of gastritis at ​​Puskesmas Biru in Bone Regency in 2019. Suggestions for the people to adopt a healthy lifestyle in order to avoid gastritis and to the next researcher to be able to develop research related to gastritis so that references related to the causal relationship of this disease can develop.